Analysis of the aqueous humor before and after the administration of faricimab in patients with nAMD - Ryo Nonogaki; Hikaru Ota; Jun Takeuchi; Yuyako Nakano; Ai Fujita Sajiki; Takahito Todoroki; Koichi Nakamura; Hiroki Kaneko; Koji M. Nishiguchi (Scientific Reports)
Abstract This study aimed to evaluate the changes in cytokine levels in the aqueous humor and factors of treatment resistance following intravitreal faricimab injection in treatment-naïve patients with neovascular age-related macular degeneration. A total of 32 eyes were analyzed before and after a single faricimab injection. Although the best-corrected visual acuity (BCVA) showed no significant improvement, the mean central retinal thickness decreased significantly by 73.7% (P < 0.01), and more than 90% of the eyes showed improvement in exudative changes 1 month after faricimab injection. Moreover, the aqueous humor concentrations of vascular endothelial growth factor (VEGF)-A, angiopoietin (Ang)-2, and placental growth factor considerably decreased 1 month after faricimab injection. Multivariate analyses adjusted for age, sex, BCVA, central choroidal thickness, and aqueous humor cytokines revealed that higher Ang-2 levels in the aqueous humor at baseline were associated with better treatment response to faricimab injection. These findings suggest that the dual inhibition of VEGF-A and Ang-2 by faricimab is effective in reducing exudative changes and that Ang-2 may serve as a potential biomarker for predicting faricimab treatment response.